2018
DOI: 10.1080/03009742.2018.1464206
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of a multi-biomarker disease activity score for clinical remission and radiographic progression in patients with early rheumatoid arthritis: a post-hoc study of the OPERA trial

Abstract: Early changes in MBDA score were associated with clinical remission based on DAS28-CRP at 6 months. In anti-CCP-positive patients, a non-high baseline MBDA score (≤ 44) had a clinical value by predicting very low risk of radiographic progression at 12 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 17 publications
0
31
1
Order By: Relevance
“…Cross-classification analyses showed that the MBDA score predicted risk for radiographic progression even when it was discordant with DAS28-CRP or CRP, such as when the MBDA score was high and conventional measures indicated low disease activity 14 . Multivariate analyses showed that the MBDA score was the strongest independent predictor of radiographic progression, compared with DAS28-CRP, CRP and other risk factors for radiographic progression 9,10,13,14 .…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…Cross-classification analyses showed that the MBDA score predicted risk for radiographic progression even when it was discordant with DAS28-CRP or CRP, such as when the MBDA score was high and conventional measures indicated low disease activity 14 . Multivariate analyses showed that the MBDA score was the strongest independent predictor of radiographic progression, compared with DAS28-CRP, CRP and other risk factors for radiographic progression 9,10,13,14 .…”
Section: Introductionmentioning
confidence: 94%
“…The CRP categories employed here were low 10 mg/L, moderate >10-30 mg/L and high >30 mg/L, to be consistent with prior publications on the MBDA score 10,14 and with the ACR/EULAR definition of Boolean remission (CRP < 10 mg/L) 18 . CRP data was obtained from published results 10 or from patient-level data 9,12 , if available.…”
Section: Clinical Measuresmentioning
confidence: 99%
See 3 more Smart Citations